What lies beneath . . . Late Glacial human occupation of the submerged North Sea landscape. (9th February 2018) - Amkreutz, Luc; Verpoorte, Alexander; Waters-Rist, Andrea; Niekus, Marcel; van Heekeren, Vivian; van der Merwe, Alie; van der Plicht, Hans; Glimmerveen, Jan; Stapert, Dick; Johansen, Lykke
Abstract: Abstract : Archaeological evidence from the submerged North Sea landscape has established the rich diversity of Pleistocene and Early Holocene ecosystems and their importance to hunter-gatherer subsistence strategies. Comparatively little of this evidence, however, dates to the Late Glacial, the period when Northern Europe was repopulated by colonising foragers. A human parietal bone and a decorated bovid metatarsus recently recovered from the floor of the North Sea have been dated to this crucial transitional period. They are set against the background of significant climatic and environmental changes and a major technological and sociocultural transformation. These discoveries also reaffirm the importance of continental shelves as archaeological archives.